A Rare Bilateral Presentation of Multiple Dens Invaginatus, Shovel-Shaped Incisor and Talon Cusp With Mesiodens - Hegde, S; Jain, M; Shubha, AB (Kathmandu University Medical Journal, 2015)
The aim of this paper is to describe a unique and unusual case of concomitant appearance of morphological dental anomalies in the maxillary anterior region, along with its management in a patient with no systemic abnormality. This case report describes the clinical and radiographic features of talon cusp, dens invaginatus, shovel-shaped incisors and a supernumerary tooth occurring in a single patient, which is a rare presentation. All 4 permanent maxillary incisors had dens invaginatus, the permanent maxillary canines showed the presence of talon cusps, the permanent maxillary central incisors were shovel-shaped and an erupted mesiodens was also observed. Treatment included restorative, surgical and orthodontic approaches. Kathmandu University Medical Journal Vol.12(4) 2014; 292-295